1998
DOI: 10.2337/diacare.21.11.1889
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of glucose tolerance categories according to World Health Organization and American Diabetes Association diagnostic criteria in a population-based study in Brazil. The Japanese-Brazilian Diabetes Study Group.

Abstract: Although the number of diabetic subjects was similar between the criteria, those identified as being at risk for diabetes were quite distinct. Fewer subjects were classified as having IFG by ADA criteria than as having IGT by WHO criteria. Abnormal glucose tolerance based on WHO criteria seems to identify a worse cardiovascular profile than abnormal tolerance based on ADA criteria. Follow-up studies are necessary to know the prognostic significance of IFG to predict subsequent diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
36
1
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 5 publications
8
36
1
1
Order By: Relevance
“…and increased basal hepatic glucose output, whereas subjects with isolated post-load hyperglycaemia have decreased peripheral insulin sensitivity. 8,12,15 There is evidence that such metabolic differences may be relevant from a clinical standpoint: patients with post-load hyperglycaemia have worse cardiovascular risk profiles 10,24 and increased death risks.…”
Section: Discussionmentioning
confidence: 99%
“…and increased basal hepatic glucose output, whereas subjects with isolated post-load hyperglycaemia have decreased peripheral insulin sensitivity. 8,12,15 There is evidence that such metabolic differences may be relevant from a clinical standpoint: patients with post-load hyperglycaemia have worse cardiovascular risk profiles 10,24 and increased death risks.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a protracted and controversial debate on this point and it is summarized in detail elsewhere [65,76,77]. What is not disputed is that the chronic hyperglycaemia of diabetes is associated with long-term damage and dysfunction of various organs, especially the retina, kidney, nerves and cardiovascular system [35, 76,77].…”
Section: Screening For Diabetesmentioning
confidence: 99%
“…Diabetes and glucose intolerance have been established as major risk factors for cardiovascular disease and total mortality in the Honolulu Heart Program and other middle-aged populations (3)(4)(5)(6)(7)(8)(9). During the last few years, several reports have compared the prevalence of diabetes and cardiovascular risk factors using the World Health Organization (WHO) 1998 (10) and American Diabetes Association (ADA) 1997 (11) classifications (12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Most of these studies have shown that substantially more subjects with diabetes are identified when the 2-h postload glucose is used in addition to the fasting glucose and suggest that there is value in using the postload measurement.…”
mentioning
confidence: 99%